Weed Control With ImiFlex in Igrowth Forage Sorghum - R. S. Currie; P. W. Geier; S. H. Lancaster; C. M. Weber (Kansas Agricultural Experiment Station Research Reports, 2023)
Igrowth (imidazolinone-resistant) forage sorghum hybrids were recently commercialized in Kansas. Even though the active ingredient of the herbicide associated with these systems, imazamox, is used in other crops, data are needed to define best practices for use in forage sorghum. The objective of experiments in Manhattan and Garden City, KS, was to investigate the use of ImiFlex (imazamox) herbicide in Igrowth (imidazolinone-tolerant) forage sorghum. At Garden City, volunteer corn and johnsongrass control 29 days after treatment was 90% or greater in all treatments that included ImiFlex. Similarly, Palmer amaranth control 28 days after treatment was 91% or greater at Manhattan. Forage sorghum injury (5%) was noted 18 days after treatment in Manhattan, however, by 28 days after treatment plants had recovered. These results suggest that Igrowth forage sorghum may help Kansas farmers manage troublesome weeds; however, proper stewardship of the technology will be necessary.
Keywords: Herbicide-resistant; Palmer amaranth; johnsongrass